quantum chemical and experimental insight into structure, physicochemical properties and dissolving behavior of deep eutectic solvents - Zhang, Yuling (World Scientific, 2022)
During the past decade, deep eutectic solvents (DESs), emerging as green, versatile and adjustable alternatives to traditional solvents, have attracted intensive interests and immense research in various research fields. Especially DESs show quite a remarkable potential dissolving capability, due to their ability to donate as well as accept protons and electrons. A thorough and deep understanding of the microstructure, interactions and dissolving mechanism within DESs plays a key role in acquiring a task-specific DES. Quantum chemistry (QC) calculations provide structure-property-function relationship based on the molecular description and make up for the limitations of the current experimental techniques, showing promises for DESs screening and design. This paper summarizes the current research involving QC calculations and combined experiments, on investigating the structure, physicochemical properties and dissolving capability of DESs from the macroscopic and microcosmic perspective. This paper highlights and discusses the dissolving mechanism of various compounds in DESs, covering the recent successes in applying QC calculations to select the appropriate DESs as dissolving media. Furthermore, a brief analysis of perspectives and challenges for the future research in this field is presented. It is expected that this paper will inspire the future development of DESs from synthesis design to various designated applications.